You can do it! - Stephens, Elle; Fruchter, Jason; Nickelodeon (Firm) (New York Random House, 2020)
Practicing for the skateboard contest, Penny and Rod support their friend Brody, who navigates high expectations while trying to master a big jump
"Based on the teleplay "Big swirl games" by Scott Albert."
At head of title: Nickelodeon Top Wing
English Stories
Preschool - Kindergarten
Keywords: Birds -- Juvenile fiction; Contests -- Juvenile fiction; Friendship -- Juvenile fiction; Skateboarding -- Juvenile fiction; Birds -- Fiction; Contests -- Fiction; Friendship -- Fiction; Skateboarding -- Fiction; Birds; Contests; Friendship; Skateboarding; Children's stories; Readers; Fiction; Juvenile works; Readers (Publications); Readers (Publications); Readers